Virtual screening of natural products as potential inhibitors of SARS-CoV-2 main protease, RNA-dependent RNA polymerase (RdRp) and Spike Protein: Database design, molecular docking and molecular dynamic study - Motahareh Boozari; Zeinab Amiri Tehranizadeh; Hossein Hosseinzadeh (Avicenna Journal of Phytomedicine)
Objective: COVID-19 is caused by the SARS-CoV-2 virus. In this study, around 300 herbal compounds were screened virtually to find the best anti-COVID-19 structures. Materials and Methods: An extensive search in electronic databases was done. Around 300 herbal compounds, which were previously proven to be antiviral structures, were extracted from articles and considered our primary database. Then, molecular docking studies were performed to find the best inhibitors of the main SARS-COV-2 proteins, including spike protein (PDB 7BWJ), RNA-dependent RNA polymerase (PDB 6M71) and main protease (PDB 5R7Z).Results: The molecular docking and dynamics studies revealed that fangchinoline as an alkaloid could bind to the main protease of the virus more potent than lopinavir (-42.26 vs. -30.9 kJ/mol). Fangchinoline can be orally active based on drug-like properties. According to the molecular dynamic study, the complex between the fangchinoline and SARS-CoV-2 main protease is stable. chebulagic acid is a benzopyrene tannin that could inhibit RNA-dependent RNA polymerase (RdRp) better than remdesivir (-43.9 vs. -28.8 kJ/mol). The molecular dynamic study showed that chebulagic acid-RdRp interaction is stable and strong. Furthermore, suramin could neutralize different variants of COVID-19 spike proteins (wild type, and alpha and beta variants). However, suramin is not orally active but it is a potential inhibitor for different coronavirus spike proteins. Conclusion: According to the promising in silico results of this study, fangchinoline, chebulagic acid and suramin could be introduced as potential lead compounds for COVID-19 treatment. We are hopeful to find a reliable remedy shortly through natural compounds.